Diversity gradients of terrestrial vertebrates – substantial variations about a common theme - Raz, T. (2023)
Environmental factors, such as temperature, precipitation, and elevation, explain most of the variation in species richness at the global scale. Nevertheless, richness patterns may have different drivers across taxa and regions. To date, a comprehensive global examination of how various factors such as climate or topography drive patterns of species richness across all terrestrial vertebrates, using the same methods and predictors, has been lacking. Recent advances in species-distribution data allowed us to model and examine the richness pattern of all terrestrial tetrapods comprehensively. We tested the relationship between environmental and biogeographical variables and richness of amphibians (5983 species), birds (9630), mammals (5004), reptiles (8939), and tetrapods as a whole, globally, and across biogeographical realms. We studied the effects of climatic, ecological, and biogeographic drivers using generalized additive models. Richness patterns and their environmental associations varied among taxa and realms. Overall precipitation was the predominant richness predictor. However, temperature was more important in realms where both cold and warm conditions exist. In the Indomalayan realm, elevational range was very important. Richness patterns of mammals, birds, and amphibians were strongly related to precipitation whereas reptile richness was mostly associated with temperature. Our results support the universal importance of precipitation but also suggest that future global-scaled research should incorporate other relevant variables other than climate, such as elevational range, to gain a better understanding of the richness–environment relationship. By doing so, we can further advance our knowledge of the complex relationships between biodiversity and the environment.